1999
DOI: 10.1007/s002590050475
|View full text |Cite
|
Sign up to set email alerts
|

Single-photon emission tomography of a computerised model of pulmonary embolism

Abstract: Planar pulmonary scintigraphy is currently the standard investigation for the diagnosis of pulmonary embolism. There are a number of problems with the technique, particularly in patients with an intermediate scan report under the PIOPED criteria. The technique is also under threat from the increasing use of spiral CT angiography. A putative improvement may be gained by use of tomography. The incremental value of tomography over planar studies was therefore evaluated in a virtual model of pulmonary scintigraphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Embolic defects may not be detected if there is shine-through from underlying lung segments with normal perfusion, thus resulting in an underestimation of the extent of perfusion loss (4). Furthermore, the medial basal segment of the right lower lobe is often not visualized on planar scans (2,5). Added to these factors is the widespread use of probabilistic reporting criteria, and a relatively high indeterminate rate, both of which have caused significant dissatisfaction among referring physicians (6,7).…”
mentioning
confidence: 99%
“…Embolic defects may not be detected if there is shine-through from underlying lung segments with normal perfusion, thus resulting in an underestimation of the extent of perfusion loss (4). Furthermore, the medial basal segment of the right lower lobe is often not visualized on planar scans (2,5). Added to these factors is the widespread use of probabilistic reporting criteria, and a relatively high indeterminate rate, both of which have caused significant dissatisfaction among referring physicians (6,7).…”
mentioning
confidence: 99%
“…It has been shown that overlapping structures result in image worsening when planar imaging is used [20,21] and this is particularly true in lung scan where numerous segments are entangled. SPECT enables to get rid of most of the environment when analysing a specific zone and the visual comfort brought by its use is obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evaluation of SPECT imaging applied to ventilatiodperfusion scintigraphy has suggested that it may further improve the accuracy of the scintigraphic diagnosis of PE. 18 The continuing improvement of the various imaging technologies, particularly if faster assessment of the thorax becomes routinely available with helical CT, suggests that further outcomeoriented studies of their application to diagnosis of PE are to be encouraged. It is reasonable to hope that they will ultimately lead to significant further reduction in uncertainties surrounding …”
Section: \mentioning
confidence: 99%